Decision Support System for Selection of Quality Palm Seeds with the Analytical Hierarchy Process Method - Putra, Almi Wijaya (Universitas Putra Indonesia YPTK Padang, 2023)
At PT. Gersindo, which is located in West Pasaman Regency, is a factory company that processes palm fruit into semi-finished oil or often called CPO (Crude Palm Oil). The main part that is managed in oil palm is the fruit, the fruit of the oil palm produces crude oil. PT. Gersindo is currently still using the manual method in determining the quality of the oil palm kernels, so that problems arise in the selection of the oil palm kernels at PT. Gersindo. At the factory PT. Gersindo in selecting quality palm kernels can be solved by developing an application in a decision support system. A decision support system is a system that is able to solve problems efficiently and effectively, which aims to help make decisions by choosing various alternative decisions. One technique that can be applied in developing a decision support system is to use the AHP ( Analytical Hierarchy Process ) method. The AHP method is a method in a decision support system for solving a very complex and unstructured problem into several component parts in a hierarchical arrangement by giving subjective values. The essence of the AHP method is to determine the weight value for each criterion. The results of this study can be determined Consistency Ratio (CR) is 0.0705 . And CR is less than 0.1 , then the matrix is declared consistent, so it is very effective and efficient in making decisions on selecting quality palm kernels.